Assessment of the capacity of health facilities in the early detection of disabilities in children in the Brong Ahafo Region of Ghana - Yinbil, Joseph Baba (2017)
A Thesis submitted to the Department of Community Health, College of Health Sciences In partial fulfillment of the requirements for the degree of Master of Science (Disability, Rehabilitation, and Development),.